Comparative pathogenicity of Aeromonas spp. in cultured Red Hybrid Tilapia (Oreochromis niloticus × O. mossambicus) - Sayuti, Mohamad Azzam; Md Yasin, Ina Salwany; Saad, Mohd Zamri; Annas, Salleh; Yusof, Mohd Termizi; Monir, Md Shirajum; Mohamad, Aslah; Muhamad Sofie, Mohd Hafiz Ngoo; Lee, Jing Yie; Chin, Yong Kit; Zahaludin, Muhammad Amir Danial; Addenan, Nurul Asyiqin; et al. (Multidisciplinary Digital Publishing Institute, 2021)
The genus Aeromonas has been recognised as an important pathogenic species in aquaculture that causes motile Aeromonas septicaemia (MAS) or less severe, chronic infections. This study compares the pathogenicity of the different Aeromonas spp. that were previously isolated from freshwater fish with signs of MAS. A total of 124 isolates of Aeromonas spp. were initially screened for the ability to grow on M9 agar with myo-inositol as a sole carbon source, which is a discriminatory phenotype for the hypervirulent A. hydrophila (vAh) pathotype. Subsequently, LD50 of six selected Aeromonas spp. were determined by intraperitoneal injection of bacterial suspension containing 103, 105, and 107 CFU/mL of the respective Aeromonas sp. to red hybrid tilapias. The kidneys, livers and spleens of infected moribund fish were examined for histopathological changes. The screening revealed that only A. dhakensis 1P11S3 was able to grow using myo-inositol as a sole carbon source, and no vAh strains were identified. The LD50–240h of A. dhakensis 1P11S3 was 107 CFU/mL, while the non-myo-inositol utilizing A. dhakensis 4PS2 and A. hydrophila 8TK3 was lower at 105 CFU/mL. Similarly, tilapia challenged with the myo-inositol A. dhakensis 1P11S3 showed significantly (p < 0.05) less severe signs, gross and histopathological lesions, and a lower mortality rate than the non-myo-inositol A. dhakensis 4PS2 and A. hydrophila 8TK3. These findings suggested that myo-inositol utilizing A. dhakensis 1P11S3 was not a hypervirulent Aeromonas sp. under current experimental disease challenge conditions, and that diverse Aeromonas spp. are of concern in aquaculture farmed freshwater fish. Therefore, future study is warranted on genomic level to further elucidate the influence of myo-inositol utilizing ability on the pathogenesis of Aeromonas spp., since this ability correlates with hypervirulence in A. hydrophila strains.